Theory Of English Constant In Phonology - Najah Athirah; Sabila Kamalia; Yani Lubis (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The theory of consonants in English phonology is an important aspect in understanding the sound system in that language. Phonology is the study of how the sounds in language are used to form meaning. In English, consonants and vowels have different roles in forming word structure and sound articulation.Consonants in English are defined as sounds that experience resistance or airflow shift when spoken. There are various types of consonants in English, such as hissing consonants, popping consonants, sliding consonants, and so on. These consonants have certain characteristics, such as the place and manner of articulation, which distinguish one consonant from another.Places of articulation refer to the parts in the mouth or throat that are used to produce consonant sounds. For example, the lips, teeth, tongue, palate, and throat can play a role in the production of consonants. For example, the consonant /p/ is pronounced by bringing the lips together, while the consonant /k/ is pronounced by moving the back palate with the back of the tongue.The manner of articulation refers to the type of resistance or shift in airflow that occurs when pronouncing the consonant. Some examples of how consonants are articulated in English include complete closure of the airflow (eg /p/), partial obstruction of the airflow (eg /s/), or passage of air through the nose (eg /m/). The theory of consonants and vowels in English phonology helps to explain how these sounds form a distinctive language system. Knowledge of the place and manner of consonant articulation, as well as the position of the tongue and the tilt of the vowel lips, allows linguistics to analyze the differences in sounds in English. In the study of phonology, this theory also helps to understand sound patterns, sound changes, and the placement of sounds in words as well as in the broader structure of language.